Cambio climático, ordenación del territorio y sostenabilidad urbana en España - Yábar Sterling, Ana (Observatorio Medioambiental, 2007)
Urban environmental management and urban sustainability are highly related to spatial planning models and several other long term and strategic action plans at the local, metropolitan, regional or national levels depending also on their coordination. Local policies for urban environmental protection, GHG mitigation policies focused within city’s area and therefore, urban sustainability policies undertaken by local authorities are also strongly correlated. The EU Thematic Strategy for Urban Environment sets that out and considers urban transport and construction the main sectors for climate mitigation local policies; those and also, sustainable urban design and management are the big issues considered in the EU Strategy to enhance policy cooperation at the different administrative levels in order to reach urban sustainability. Spanish local authorities (CCLL) over 50.000 people are legally dealing with environmental urban matters. Some CCLL —over and under that threshold— signed the Aalborg Commitments in favour of local sustainability; besides, some belongs to Spanish Cities for Climate Network (RECC). The paper shows absolute and relative data on those respects —in relation to the amount of municipalities and population figures, in aggregated and regional terms— in order to asses on the formal involvement degree for CCLL with local sustainability and climate GHG mitigation for urban sources. Finally, additional information is considered on the CCLL integration on Spanish regional or departmental networks for local sustainability as well as other information on local planning initiatives or cross cutting environmental issues related to urban areas.